Determining the Predictive Power of Vitamin D Levels in Iron Deficiency Anemia - Sorush Niknamian (Britain International for Academic Research (BIAR) Publisher, 2019)
Background:Iron deficiency anemia is one of the most common hypochromic microcytic anemias and nutritional disorders in today’s world. Vitamin D is an important steroid hormone for the metabolism of serum calcium and phosphorus and plays a major role in the function of various body systems. Evidence suggests that vitamin D deficiency is associated with iron deficiency anemia. We aimed to compare the serum level of vitamin D between children with iron deficiency anemia and healthy ones. Methods: This case-control study was conducted on 60 patients with iron deficiency anemia and 60 healthy ones who did not suffer from iron deficiency anemia. Patients participated in the study voluntarily. Vitamin D levels were measured using HPLC and ferritin by RIA method. To estimate the predictive value of vitamin D levels in iron deficiency anemia, ROC curve analysis was used. Results: In this study, 120 children aged 6-144 months with mean age of 30.2±31.4 months were analyzed; 49.2% of them were boys and 50.8% were girls. Vitamin D levels varied from 4.8 to 63.2 ng/ml with a mean of 23.87±12.57 ng/ml in all patients (19.25±9.15 ng/ml in the case group and 28.48±13.84 ng/ml in the control group (P<0.001). In other words, patients with a vitamin D level <23.6 ng/ml should be investigated for iron deficiency anemia, and sufficient vitamin D had a protective effect on iron deficiency anemia and each unit increase in vitamin D decreased the chance of iron deficiency anemia by 7.8%. Conclusion: The prevalence of simultaneous iron deficiency anemia and vitamin D deficiency is very high in children and there is a significant relationship between serum levels of 25(OH)D and hemoglobin.